TAP Sampling for Asian Citrus Psyllid (ACP) Field Sheet - Phil Stansly; Jawwad A. Qureshi (EDIS)
This new field sheet provides information on Tap sampling for Asian Citrus Psyllid (ACP). Monitoring ACP populations is an important tool in the integrated management of citrus greening. The most efficient way to estimate field populations of this insect is by monitoring adults. Tap sampling has proven to provide data needed to make informed decisions for managing this insect pest. Written by Phil Stansly and Jawwad A. Qureshi, and published by the Entomology and Nematology Department, January 2016.